Over her dead body eaudiobook Bailey weggins series, book 4. - White, Kate (Bailey Weggins Mystery, 2017)
New York Times best-selling author Kate White, editorin- chief at Cosmopolitan, knows the glossy magazine world like the back of her hand. Her Bailey Weggins mystery series serves head-scratching whodunits with healthy dollops of dishy dirt. Fired from her job at Gloss, Bailey lands a new gig at celebrity gossip mag Buzz. When her slave-driving boss is murdered, Bailey investigates. Her friend and co-worker Robby is the chief suspect-but there's a long list behind him.